"Чотири кольори буття" Любові Баранової (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article deals with Lubov Baranova 's use of colours as a poetic device. The author characterizes the «spectrum of colours « and explains the semantics of colour names and defines their stylistic function in Lubov Baranova works.